Molecular characterization of Mycoplasma synoviae in chickens in South Africa using single-stranded conformation polymorphism and high-resolution melting curve analysis of the vlhA gene - Venter, Estelle Hildegard (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.